2019
DOI: 10.26656/fr.2017.4(2).283
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anthocyanin encapsulation efficiency into yeast cell by plasmolysis, ethanol, and ultrasound treatments using alone or in combination

Abstract: Anthocyanin is a water-soluble color compound of the flavonoid which was successfully encapsulation in Saccharomyces cerevisiae by plasmolysis, ethanol, and ultrasound treatments using alone or in combination in the first time. Treatment agents significantly enhanced the encapsulation efficiency of anthocyanin fluid. The encapsulation yield (EY) of the combined factors was higher than the individual impact factors. Ethanol 10% (v/v) and ultrasound 180 seconds for the highest EY 40.22±0.67%, then ethanol 10% (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Similarly, the encapsulation in chitosan coated alginate-starch capsules also enhanced Lactobacillus acidophilus and Bifidobacterium pseudocatenulatum viability by 3.4 log CFU/mL and 5.43 log CFU/mL, respectively, which were higher than the non-encapsulation cell after 30 min incubation in 60 °C [25]. Besides, the encapsulated anthocyanins by yeast cells were stable in colors under the influence of temperature compared to unencapsulated color solutions [16]. The ability to protect L. plantarum from SGF condition by S. cerevisiae cells was significantly effective compared to the control (Table 1).…”
Section: The Viability Of L Plantarum During the Muffin-baking Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the encapsulation in chitosan coated alginate-starch capsules also enhanced Lactobacillus acidophilus and Bifidobacterium pseudocatenulatum viability by 3.4 log CFU/mL and 5.43 log CFU/mL, respectively, which were higher than the non-encapsulation cell after 30 min incubation in 60 °C [25]. Besides, the encapsulated anthocyanins by yeast cells were stable in colors under the influence of temperature compared to unencapsulated color solutions [16]. The ability to protect L. plantarum from SGF condition by S. cerevisiae cells was significantly effective compared to the control (Table 1).…”
Section: The Viability Of L Plantarum During the Muffin-baking Processmentioning
confidence: 99%
“…Saccharomyces cerevisiae is generally regarded as safe (GRAS), easy to scale at low cost, and available in the market [13]. Previous studies have shown the potential of Saccharomyces cerevisiae in the microencapsulation of compounds such as chlorogenic acid, curcumin, anthocyanin, etc [14][15][16]. But so far, the use of Saccharomyces cerevisiae cells for probiotic microencapsulation has been very little reported.…”
Section: Introductionmentioning
confidence: 99%